2004
DOI: 10.1126/science.1093712
|View full text |Cite
|
Sign up to set email alerts
|

Cdh1-APC Controls Axonal Growth and Patterning in the Mammalian Brain

Abstract: The anaphase-promoting complex (APC) is highly expressed in postmitotic neurons, but its function in the nervous system was previously unknown. We report that the inhibition of Cdh1-APC in primary neurons specifically enhanced axonal growth. Cdh1 knockdown in cerebellar slice overlay assays and in the developing rat cerebellum in vivo revealed cell-autonomous abnormalities in layer-specific growth of granule neuron axons and parallel fiber patterning. Cdh1 RNA interference in neurons was also found to override… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
391
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(409 citation statements)
references
References 22 publications
14
391
1
3
Order By: Relevance
“…One elegant mechanism has been defined involving the anaphase promoting complex (APC), which functions as an E3 ubiquitin ligase in the regulation of cyclins and other mediators of cell-cycle control. In postmitotic neurons, APC and its activator protein, Cdh1, stimulate degradation of the transcription factor SnoN (Konishi et al 2004;Stegmuller et al 2006). SnoN levels are also regulated by TGF-b/SMAD-2 signaling (Stegmuller et al 2008).…”
Section: Transcription Regulatorsmentioning
confidence: 99%
“…One elegant mechanism has been defined involving the anaphase promoting complex (APC), which functions as an E3 ubiquitin ligase in the regulation of cyclins and other mediators of cell-cycle control. In postmitotic neurons, APC and its activator protein, Cdh1, stimulate degradation of the transcription factor SnoN (Konishi et al 2004;Stegmuller et al 2006). SnoN levels are also regulated by TGF-b/SMAD-2 signaling (Stegmuller et al 2008).…”
Section: Transcription Regulatorsmentioning
confidence: 99%
“…As in the budding yeast model, where the first phase of Clb2 degradation by APC Cdc20 (Ba¨umer et al, 2000;Yeong et al, 2000;Wa¨sch and Cross, 2002) is already sufficient for most aspects of mitotic exit (Wa¨sch and Cross, 2002), the main role of Cdh1 perhaps in concert with CKIs like p21 and p27 in mammalian cells is also very likely the regulation of a stable G1 and accurate DNA replication by keeping mitotic cyclins low during G1 (Figure 3). APC Cdh1 may also play an important role in differentiation, since it controls axonal growth and morphogenesis in postmitotic neurons in mammalian cells (Konishi et al, 2004). APC Cdh1 has also been linked to TGF -mediated control of cell growth and differentiation (Stroschein et al, 2001;Wan et al, 2001).…”
Section: Proteolysis and Cell Cycle Controlmentioning
confidence: 99%
“…Konishi et al (2004) has shown that anaphase promoting complex plays an important role in transcriptional regulation of axon growth. This complex is a multisubunit ubiquitin ligase that functions in mitotic cells to promote cell cycle exit via degradation of cyclins and other regulators of cell cycle progression (see Murray 2004 for a recent review).…”
Section: Genetic Control Of Axon Growthmentioning
confidence: 99%